Terorisme, Radikalisme dan Fundamentalisme - Azyumardi Azra (SIASAT, 2018)
This article argues, terrorist cell germination occurs because of people in the community who don't want to care or even protect terrorists. There are even community members who take them as sons-in-law. No wonder then that they are very hard to find; and once the place where they kissed the authorities, they had already fled to another place that was not known to security officials. Therefore, once again, the collaboration of all levels of society, the government and various related ministries, security forces, mass organizations, and social leadership is absolutely essential in combating terrorism. Terrorism for any reason cannot be justified; and terrorism is one of the most naked forms of crime against humanity.